Longitudinal-vertical integrated cooperative control of distributed drive electric vehicle considering optimization of energy economy and comfort - Jia, Yuan; Liu, Yonggang; Zhang, Yuanjian; Chen, Zheng; Zhang, Yi (Energy (Oxford), 2025)
The interdependent mechanisms among energy economy, longitudinal-vertical dynamics, and torque distribution coordination in distributed-drive electric vehicles are still not fully understood or effectively managed, particularly when subjected to external stochastic road excitations. To address this problem, this study proposes a distributed collaborative control architecture based on longitudinal-vertical coupling torque distribution and suspension control to balance vehicle energy efficiency and ride comfort. First, the interaction between the torque distribution coefficient and vehicle pitch motion under various acceleration conditions is systematically analyzed using a semi-vehicle model. Subsequently, a dynamic programming algorithm is employed to perform offline optimization of the torque distribution coefficient, with the dual objectives of enhancing energy economy and ride comfort. Then, to enhance the robustness of vertical control under road irregularity excitations and reduce the complexity of centralized control across varying acceleration conditions, a quarter-suspension control strategy based on robust model predictive control is proposed. Specifically, to ensure online decision-making of torque distribution coefficients and rapid prediction of acceleration, a light gradient-boosting machine-based online decision model is designed. Finally, the results confirm that the proposed strategy significantly outperforms existing centralized and decoupled control methods, delivering remarkable enhancements in both energy economy (with an improvement of ≥17.4 %) and ride comfort (e.g., an 85.5 % reduction in pitch acceleration). •Designing a cooperative active suspension and torque allocation control structural.•Proposing an energy-comfort-oriented torque allocation via longitudinal-vertical coupling.•Developing a real-time longitudinal acceleration predictor under road stiffness disturbances.•Proposing an RMPC suspension control strategy based on axle load transfer.